Low‐temperature silane coupling agent modified biomimetic micro/nanoscale roughness hierarchical structure superhydrophobic polyethylene terephthalate filter media. (9th February 2022) - Dong, Wei; Zhou, Shian; Qian, Fuping; Li, Qing; Tang, Gang; Xiang, Tengfei; Long, Hong‐ming; Chun, Tiejun; Lu, Jinli; Han, Yunlong
Abstract: A hierarchical structure similar to "lotus leaf surface" has attracted widespread attention due to its excellent hydrophobic properties. Herein, using low‐temperature sol–gel method prepared superhydrophobic SiO2 particles with biomimetic lotus leaf micro/nanoscale hierarchical structure (BRHS), which were formed in situ on the surface of polyethylene terephthalate (PET) fiber, and endowing PET‐based composite filter media (P‐Filter) superhydrophobic property. After different TEOS@MTES@ KH550 (TMK) modification treatments, SiO2 particles were wrapped on the P‐Filter, and the microscopic pore structure was changed significantly. When the mass ratio of TEOS/MTES (TM) reached 4/2, KH550 modified SiO2 nanoparticles displayed the widest particle size distribution. In this case, the PET (TMK@PET‐4) fibers exhibited rough morphology of BRHS, the contact angle (WCA) reached 160.9 ± 2.8°, and the shedding angle (WSA) was 5.9 ± 2.5°, which reaching a superhydrophobic state. Also, the TMK@PET‐4 filter material demonstrated best comprehensive filtration performance for PM 0.3 ( η : 99.12%, Δ P : 58 Pa, Q F : 0.0816), 36.96% higher than the original PET filter, and had excellent mechanical stability and self‐cleaning properties. Therefore, the presented simple method has a guiding significance in producing superhydrophobic P‐Filter, a potential value for the research and development of bag‐type dust removal materials in high‐humidity environments.